2016
DOI: 10.1113/jp272208
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cytoprotective roles of pyruvate and ATP by glucose metabolism on epithelial necroptosis and crypt proliferation in ischaemic gut

Abstract: Mesenteric ischaemia/reperfusion induces epithelial death in both forms of apoptosis and necrosis, leading to villus denudation and gut barrier damage. It remains unclear whether programmed cell necrosis [i.e. receptor-interacting protein kinase (RIP)-dependent necroptosis] is involved in ischaemic injury. Previous studies have demonstrated that enteral glucose uptake by sodium-glucose transporter 1 ameliorated ischaemia/reperfusion-induced epithelial injury, partly via anti-apoptotic signalling and maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 62 publications
(75 reference statements)
0
34
0
Order By: Relevance
“…It often follows mesentery embolism, intestinal sepsis, hemorrhagic shock, and transplantation and is thought to be the main inducer of multiple organ dysfunction syndrome [31, 32]. Intestinal I/R leads to local intestinal tissue injury and mucosal barrier dysfunction [3335] and also causes distant organ dysfunction, especially in the liver and lung [79]. Certain studies have suggested that the liver is the first organ to be damaged following the intestinal I/R, because its vasculature is coupled with the intestinal circulation [9, 11].…”
Section: Discussionmentioning
confidence: 99%
“…It often follows mesentery embolism, intestinal sepsis, hemorrhagic shock, and transplantation and is thought to be the main inducer of multiple organ dysfunction syndrome [31, 32]. Intestinal I/R leads to local intestinal tissue injury and mucosal barrier dysfunction [3335] and also causes distant organ dysfunction, especially in the liver and lung [79]. Certain studies have suggested that the liver is the first organ to be damaged following the intestinal I/R, because its vasculature is coupled with the intestinal circulation [9, 11].…”
Section: Discussionmentioning
confidence: 99%
“…The finding showed that neoalbaconol-induced necroptosis resulted in energy depletion by downregulated HK1 and HK2 levels [48]. Similarly, pyruvate has a protective role in ischaemic enterocytes; the level of pyruvate was depressed during necroptosis [49]. Moreover, the impairment of Na + /K + -ATPase was detected in cell necrosis [50], and the ATPase viabilities were inhibited obviously during necroptosis [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cancer cells were homogenized, and the supernatant was measured for DNA fragmentation by using a cell death detection ELISA kit (Roche; refs. 19,20,31,32).…”
Section: Measurement Of Cell Apoptosismentioning
confidence: 99%